Perbandingan Dinamika Kelembagaan Ekonomi Islam antara Indonesia, Arab Saudi, dan Thailand: Analisis terhadap Perkembangan dan Tantangan di Era Modernisasi - Cintya, Putri; Naufal Luthfi Alifa (Al Rikaz: Jurnal Ekonomi Syariah, 2025)
This study compares Islamic economic institutions in Indonesia, Saudi Arabia, and Thailand through four focuses: (1) institutional profile, (2) development dynamics, (3) regulatory and literacy challenges, and (4) reflection on Islamic economic growth. Using a comparative qualitative approach through literature review, the study finds that Indonesia leads in digitalization, Saudi Arabia shows institutional maturity aligned with Vision 2030, while Thailand remains in early development. Collaboration among governments, financial institutions, and communities is key to creating an inclusive and sustainable Islamic economic system. Indonesia continues to strengthen its ecosystem through digital innovation. Overall, the study highlights the importance of harmonizing regulation, improving human capital, and enhancing cross-country cooperation to reinforce institutional resilience and advance sustainable Islamic economic development.